Chronic exposure of nanomolar MC-LR caused oxidative stress and inflammatory responses in HepG2 cells. (February 2018) - Ma, Junguo; Li, Yuanyuan; Duan, Hongying; Sivakumar, Rajeshkumar; Li, Xiaoyu
Abstract: Low dose but long-term exposure of microcystin-LR (MC-LR) could induce human hepatitis and promote liver cancer according to epidemiological investigation results, but the exact mechanism has not been completely elucidated. In the present study, a chronic toxicity test of MC-LR exposure on HepG2 cells at 0.1–30 nM for 83 d was conducted under laboratory conditions. The western blot assay result revealed that MC-LR entered HepG2 cells, even at the concentration of 0.1 nM, after 83 d of exposure, but no cytotoxicity was observed in the HepG2 cells, as determined by the CCK-8 and LDH tests. However, the results of the DCF fluorescence assay showed that the intracellular ROS level in the 30 nM MC-LR-treated cells was significantly higher than that of the control cells, and 5 and 10 nM of MC-LR exposure totally increased the activity of SOD in HepG2 cells. These results indicate that MC-LR exposure at low concentration also induced excessive ROS in HepG2 cells. Additionally, long-term exposure of MC-LR at low concentration remarkably promoted the expression of NF-κB p65, COX-2, iNOS, TNF-α, IL-1β, and IL-6 in the cells, suggesting that long-term MC-LR exposure at low concentration can induce inflammatory reaction to HepG2 cells, which might account for MC-induced human hepatitis. Thus, we hypothesized that the pathogenesis of human hepatitis and hepatocarcinoma caused by MCs might be closely associated with oxidative stress and inflammation. Highlights: Nanomolar MC-LR entered HepG2 cells in a concentration-dependent pattern. Nanomolar MC-LR-exposure induced oxidative stress in HepG2 cells. Nanomolar MC-LR-exposure caused inflammatory reaction of HepG2 cells. Chronic exposure of MC-LR at 1 nM possessed harmful potential to HepG2 cells.